Membentuk Sumber Daya Manusia dengan Pondasi Ihsan melalui Emotional and Spiritual Quotient (ESQ) - Edi Suranta (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2021)
The Italian philosopher Macevelli, who lived in the 15th-16th century AD, proclaimed that to achieve the goal of a nation-state society to achieve the goal of all means can be taken as long as the goal is achieved, tricks, tricks, and even actions that are contrary to conscience can be done. The war of right thinking is happening at this time with the help of propaganda through electronic media and mass media as it is now, in building opinions. The influence change is so real and clear. Theories and ideas put into practice that was once politically marginalized now control the state. ESQ is here to answer the SQ theory, the fruit of Ari Ginanjar's thought as a role model for spiritual training guided by the pillars of faith and the pillars of Islam, which adorn cultural understanding and work ethic back to human nature such as love, honesty, responsibility, caring, discipline, togetherness, peace, back in orbit. Abstrak Filosuf italia Macevelli yang hidup diabad 15 – 16 M memproklamirkan bahwa untuk mencapai tujuan bermasyarakat berbangsa bernegara untuk mencapai tujuan segala cara dapat ditempuh asalkan tujuan tercapai, tipu daya, trik, bahkan tindakan yang bertentangan dengan hati nurani bisa dilakukan. Perang pemikiran benar terjadi pada saat ini dengan dibantu propaganda melalui media elektronik maupun media massa seperti sekarang, dalam membangun opini . Perubahan pengaruh sebegitu nyata dan terang benderang . Teori dan pemikiran dipraktekkan yang dulu termarjinalkan secara politik sekarang mengendalikan negara. ESQ hadir menjawab atas teori SQ buah pemikiran Ari Ginanjar menjadi role model pelatihan spiritual yang berpedoman pada rukun iman dan rukun Islam banyak menghiasi pemahaman budaya dan etos kerja kembali kepada fitrah manusia seperti kasih sayang, kejujuran, tanggungjawab, peduli, disiplin, kebersamaan, kedamaian, kembali dalam garis orbit.